Large‐scale remote fear conditioning: Demonstration of associations with anxiety using the FLARe smartphone app. Issue 7 (19th March 2021) - McGregor, Thomas; Purves, Kirstin L.; Constantinou, Elena; Baas, Johanna M. P.; Barry, Tom J.; Carr, Ewan; Craske, Michelle G.; Lester, Kathryn J.; Palaiologou, Elisavet; Breen, Gerome; Young, Katherine S.; Eley, Thalia C.
Abstract: Objectives: We aimed to examine differences in fear conditioning between anxious and nonanxious participants in a single large sample. Materials and methods: We employed a remote fear conditioning task (FLARe) to collect data from participants from the Twins Early Development Study ( n  = 1, 146; 41% anxious vs. 59% nonanxious). Differences between groups were estimated for their expectancy of an aversive outcome towards a reinforced conditional stimulus (CS+) and an unreinforced conditional stimulus (CS−) during acquisition and extinction phases. Results: During acquisition, the anxious group (vs. nonanxious group) showed greater expectancy towards the CS−. During extinction, the anxious group (vs. nonanxious group) showed greater expectancy to both CSs. These comparisons yielded effect size estimates ( d  = 0.26–0.34) similar to those identified in previous meta‐analyses. Conclusion: The current study demonstrates that remote fear conditioning can be used to detect differences between groups of anxious and nonanxious individuals, which appear to be consistent with previous meta‐analyses including in‐person studies.